Transmisi dan Transformasi Dakwah (Sebuah Kajian Living Hadis dalam Channel Youtube Nussa Official) - hayati Ridha Hayati (Jurnal Bimas Islam, 2020)
This paper highlights the Islamic animated series that lately is much loved by children and adults, namely Nussa Rara (an acronym from NusAntara). Nussa Official is a youtube channel that contains animated cartoon edutainment (educational entertainment), carrying themes about Islam which is originated from the Qur'an and Hadith. The revelations and messages of the Prophet are displayed so well that they attract attention and are easily understood by children in contrast to other animated shows in general. The focus of this research is on the theme "Basmallah" in the Youtube channel @Nussa Official. In this study the authors found: First, explicitly, the traditions referred to in this program are those that have a valid status. Second, the meaning of the recitation of basmallah is to ask for God's protection from Satan and make Satan shrink like a fly, make a routine worthy of worship, to gain blessings, to arouse enthusiasm and raise one's soul, and to provide calm. Third, the @Nussa Official youtube channel shows developments in the da'wah media or delivering hadith. The delivery of hadith or da'wah underwent a change in context from the beginning of the Prophet's time. The period of the Prophet's process of delivering the hadith starts from the oral tradition then continues on writing, painting, to social media. First is oral tradition. Something that is classified in this form is lectures, sermons, discussions, and others that are done with the tongue and voice. Second is the written tradition. Like books, journals and others. Third is painting, like calligraphy. Fourth is social media that appears on television and is now developed in the YouTube platform. The presence of the hadith recorded on the Nussa Official YouTube channel gives a new breath to the study of Islam and media-based Hadith. Therefore, itâ€™s proving that this animated series underwent transmission and transformation. So the existence of this research is expected to explain that conveying the values of goodness can be done in a variety of ways. At the same time it shows that the study of Islam, al-Qur'an and Hadith not only rests on texts or books of classical to modern interpretation but are broader than that. Keywords: Living Hadits, Daâ€™wah, Youtube, Transmission, Transformation Abstrak Tulisan ini menyoroti tentang serial animasi islami yang belakangan ini banyak digandrungi oleh anak-anak juga orang dewasa yaitu Nussa Rara (akronim dari NusAntara). Nussa Official adalah sebuah channel youtube yang berisi kartun animasi edutainment (educational entertainment), mengusung tema seputar keislaman yang bersumber dari al-Qurâ€™an dan hadis. Wahyu dan pesan Nabi ditampilkan dengan apiknya hingga menarik perhatian dan mudah dimengerti anak-anak. Berbeda dengan animasi pada umumnya yang sifatnya global. Fokus penelitian ini adalah pada tema â€œBasmallahâ€dalam channel youtube @Nussa Official. Dalam kajian ini penulis menemukan: Pertama, secara eksplisit hadis yang dirujuk dalam tayangan ini adalah hadis yang statusnya sahih. Kedua, makna dari pembacaan basmallah adalah memohon perlindungan Allah dari setan dan membuat setan mengecil bagaikan lalat, rutinitas menjadi bernilai ibadah, memperoleh keberkahan, membangkitkan semangat dan membesarkan jiwa, memberikan ketenangan. Ketiga, channel youtube @Nussa Official menunjukkan adanya perkembangan pada media daâ€™wah atau menyampaikan hadis. Penyampaian hadis maupun dakwah mengalami perubahan konteks dari awal masa Nabi. Masa Nabi proses menyampaikan hadis dimulai dari lisan. Kemudian berlanjut pada tulisan, lukisan, hingga pada media sosial. Pertama, lisan. Sesuatu yang tergolong dalam bentuk ini adalah ceramah, kuliah, diskusi, dan lainnya yang dilakukan dengan lidah dan bersuara. Kedua, tulisan. Seperti buku, jurnal dan lainnya. Ketiga, Lukisan seperti kaligrafi. Keempat, media sosial yang muncul dalam televisi dan kini berkembang dalam bentuk youtube. Hadirnya hadis yang terekam dalam channel youtube Nussa Official ini memberi nafas baru bagi kajian islam maupun hadis berbasis media. Dengan demikian membuktikan bahwa serial animasi ini mengalami transmisi dan transformasi. Maka dengan adanya penelitian ini diharapkan dapat menjelaskan bahwa menyampaikan nilai-nilai kebaikan dapat dilakukan dengan beragam. Sekaligus menunjukkan bahwa kajian keislaman, al-Qurâ€™an maupun hadis tidak hanya bertumpu pada teks atau kitab-kitab tafsir klasik hingga modern melainkan lebih luas dari pada itu. Keywords: Living Hadis, Dakwah, Youtube, Living Hadis, Transmisi, Transformasi